2016
DOI: 10.1016/j.tate.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

University teacher judgments in problem-based learning: Their accuracy and reasoning

Abstract: This study investigated the accuracy of 14 university teacher's judgments. Early in the first year, university teachers rated the chance each university student in their group would successfully complete their first year as well as the entire bachelor's program. Results show that university teachers' chance ratings were predictive of actual academic success. However, they were more accurate in predicting success than failure. Moreover, results revealed that university teachers mostly built upon their observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
1
4
1
2
Order By: Relevance
“…The fact that an aggregate score of student participation in class collected systematically in a simple scale by multiple teachers can be useful in the process of identifying potential dropouts is, to our best knowledge, an original contribution. Prior studies had already shown the potential of using tutors' information to identify struggling students (Wijnia et al 2014;O'Neill et al 2016;Wijnia et al 2016), but in these studies the tutor/ students ratio was low and, therefore, there were more frequent contacts with the students. Our study provides other contextual circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that an aggregate score of student participation in class collected systematically in a simple scale by multiple teachers can be useful in the process of identifying potential dropouts is, to our best knowledge, an original contribution. Prior studies had already shown the potential of using tutors' information to identify struggling students (Wijnia et al 2014;O'Neill et al 2016;Wijnia et al 2016), but in these studies the tutor/ students ratio was low and, therefore, there were more frequent contacts with the students. Our study provides other contextual circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, tutors are to some extent able to predict the examination performance of students in their tutor groups, although the association between tutors' predictions and subsequent academic performance and dropout is weak to moderate (Kaufman and Hansell 1997;Adam et al 2012;Wijnia et al 2014Wijnia et al , 2016. In addition, tutors seem to be better at predicting completion of the course or year than at identifying potential failure or dropout (Wijnia et al 2014(Wijnia et al , 2016, as there seems to be an overestimation of students' skills, especially for those in the lowest quartile (Whitfield and Xie 2002). The study by O'Neill et al (2016) with medical students showed that tutor daily informal observations could accurately predict student failure, albeit tutors tended to under-detect those who were at risk of failing on the following exam or drop out of the program.…”
mentioning
confidence: 99%
“…No entanto, apesar da sua relevância, o conceito de ABP pode apresentar diversos caminhos. Pode ser definida, por exemplo, em razão de sua abordagem pedagógica ativa baseada em problematizações (HUNG, 2011;GOH, 2016), ou na proposta de aprendizagem colaborativa (SMITH; HOERSCH; GORDON, 1995;WIJNIA et al, 2016).…”
Section: Abordagem Da Aprendizagem Baseada Em Problemasunclassified
“…Essa abordagem chama atenção dos pesquisadores sobre ABP em diversas frentes do conhecimento. Pesquisas avançam no aprofundamento sobre o papel do professor no processo ABP (ASSEN et al, 2016;GOH, 2014;ROTGANS;WIJNIA et al, 2016), a sua efetividade e aplicações (ALBANESE; MITCHELL, 1993;JONES et al, 2010) e a influência no desenvolvimento dos estudantes (DUNLAP, 2005;ELCIN et al, 2006;JONES et al, 2010;TAN; VAN DER MOLEN;SCHMIDT, 2016). Além de abordarem a percepção dos alunos sobre o método (AZER, 2009).…”
Section: Introductionunclassified
“…All this time, the contextual stimulations that are used to find the creative thinking skills are not optimally implemented in varieties of natural learning (IPA) such as (1) The learning model of problem based learning (Wijnia et al 2016;Allen et al 2011;Nuttariya et al 2012), (2) The Brain Based Learning (BBL) model (Eagleton & Muller 2011), (3) Inquiry model (Hong et al 2014;Lederman et al 2014;Lehtinen, 2016).…”
Section: Introductionmentioning
confidence: 99%